Analisis Efisiensi Waktu Kerja dan Kinerja SDM pada Proses Skiving di Industri Mebel Skala Kecil - Foci, Nia; Yasin, Muhamad; Munanda, M. Arif (Jurnal Manajemen Rekayasa dan Inovasi Bisnis, 2025)
This study aims to analyze work time efficiency and evaluate employee performance in the skiving process at Juned Furniture Home Industry, Pasuruan. The method employed was work sampling, with a total of 54 observations conducted on employee work activities. The results show that 89% of the time was used productively, while the remaining 11% was classified as idle. Data adequacy and uniformity tests confirmed that the number of observations met the required statistical standards. Performance evaluation using the Westinghouse Performance Rating System yielded a correction factor of +0.18, resulting in a rating factor of 1.18. This indicates that the human resources involved in the skiving process demonstrated a good level of quantitative performance. Allowance time was calculated at 9.5% of total working hours, which remains within an acceptable range. The calculation of standard time and output revealed a productivity rate of 0.15 chair designs per hour. These findings are expected to serve as a practical reference for managerial decision-making regarding work efficiency and production capacity planning in small and medium-sized furniture industries.